Analisis Evaluasi Pembelajaran Daring Pada Masa Pandemi Covid-19 di Tk Laboratorium Percontohan UPI Tasikmalaya - Nurislamy, Astri (Al-Marifah | Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This study aims to determine the implementation of learning evaluation in theKindergarten Laboratory UPI Tasikmalaya. The method used is descriptive qualitative.Data The data in this study is in the form of a descriptive text about the implementation ofonline learning during the Covid-19 pandemic at the Kindergarten of the UPI TasikmalayaPilot Laboratory which was obtained by the author from observations, interviews anddocumentation. Data sources are all things that can provide information about the data.Online learning at the UPI Tasikmalaya Pilot Laboratory Kindergarten has been carriedout since the beginning of the pandemic in 2019 until now. The evaluation process iscarried out directly during the zoom meeting. Evaluation is carried out periodically,namely daily, weekly, monthly, and yearly. The teacher makes worksheets and learningmodules every week